FEMINISME DAN TINJAUAN KRITIS TERHADAP KONSEP GENDER DALAM STUDY ISLAM - Kholil, Muhammad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2016)
Feminism is an effort gender justice requires us to make the rules fair, but gender equality does not require us to give a prize to the winner and the loser between men and women. Gender equality has become a necessity of the times. Issues these women are very regard to violence against women, sexual harassment, wage discrimination and women's rights in the workplace or a dual role as the nature of women. Some people think women with a view of ignorance before Islam came, so they do not give inheritance rights to her daughter and did not even get a part at all. They also memingitnya not work outside the home, they even ban women only weeks to study so that they assume that women who sholehah are women who never leave the house, and that means they have prevented the women to get the light of science. Yet they know that seeking knowledge is obligatory for the Muslims either male or female. Women are partners of men who were created by God with the abilities and the mental equivalent. Most of the women's movement stopped in the middle and are crossroads juaga whereas women are entitled to a space in the activity. The image of the ideal woman in the Quran is not the same as the ideal image that developed in the history of the world.